Paraurethral leomyoma: a manageable challenge - Khatuja, Ritu; Verma, Menka; Sarda, Nivedita; Chawla, Dolly; Gupta, Renu; Khare, Pratima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Leiomyoma is a most common benign tumour of uterus. But it is very rare in vagina urethral and paraurethral. There are approximately 330 case reports are available in literature and the paraurethral site is extremely uncommon. Here, we report a case of 38-year nulliparous woman presented with complain of mass coming out of vagina as well as dyspareunia. Provisional diagnosis of anterior vaginal cyst along with the differential diagnosis of paraurethral and anterior wall vaginal leiomyoma was made. Transvaginal removal of mass was done and diagnosis of paraurethral leiomyoma was confirmed by histopathology.